The Green Transition: Public Policy, Finance, and the Role of the State - Francesco Lamperti; Mariana Mazzucato; Andrea Roventini; Gregor Semieniuk (Vierteljahrshefte zur Wirtschaftsforschung, 2019)
While investments into renewable energy technologies are growing almost everywhere, the chances to meet ambitious emission and climate targets, as those envisaged in the Paris Agreement, are scant. To speed up the transition, policy makers need to design and implement a policy mix that could affect not just the quantity of green finance, but its quality as well. In this paper, we argue that a mission-oriented approach to the transition from an economy with high, to one with low greenhouse gas emissions, coupled with the state taking on the role of an entrepreneurial state, could provide an effective win-win strategy to address climate change concerns (embodied in emissions reduction and adaptation boosting) and build the basis for the next phase of growth and technological progress. In practice, this amounts to (i) abandoning the view that cost-internalization of environmental externalities would suffice to induce an effective transition (ii) developing a multi-level and cross-sectoral governance of the transition, with a clear direction in terms of the technological trajectory to favour, and (iii) designing a policy mix encompassing: fiscal instruments, targets and standards; public-private co-funding schemes; financial regulation; and disclosure practices. Social scientists should support such ambitious policy-design processes through adequate model development, where a combination of policies, and a directive role of the state, can be accommodated and examined in detail. – – Obwohl die Investitionen in erneuerbare Energietechnologien fast überall zunehmen, sind die Chancen die ehrgeizigen Emissions- und Klimaziele zu erreichen, wie sie im Pariser Abkommen vorgesehen sind, noch immer gering. Um den Übergang zu beschleunigen, müssen die politischen Entscheidungsträger einen Policy-Mix entwerfen und umsetzen, der nicht nur das Green Finance Volumen, sondern auch dessen Qualität beeinflussen könnte. In diesem Papier argumentieren wir, dass ein aufgabenorientierter Ansatz für den Übergang von einer Wirtschaft mit hohen zu einer Wirtschaft mit niedrigen Treibhausgasemissionen eine effektive Win-Win-Strategie bieten könnte. Dabei sollte der Staat die Rolle eines unternehmerischen Staates übernehmen, um die Belange des Klimawandels anzugehen (verkörpert durch Emissionsreduzierung und Anpassungssteigerung) und die Grundlage für die nächste Phase von Wachstum und technologischem Fortschritt zu schaffen. In der Praxis bedeutet dies: (i) die Auffassung wird aufgegeben, dass die Kosteninternalisierung von Umweltexternalitäten ausreichen würde, um einen effektiven Übergang herbeizuführen, (ii) eine mehrstufige und sektorübergreifende Steuerung des Übergangs mit einer klaren Ausrichtung auf die technologische Förderung wird entwickelt und (iii) ein Policy-Mix ist notwendig, der Folgendes umfasst: steuerliche Instrumente, Ziele und Standards, öffentlich-private Kofinanzierungssysteme, Finanzmarktregulierung und Offenlegungspraktiken. Sozialwissenschaftler sollten solche ehrgeizigen Politikgestaltungsprozesse durch eine angemessene Modellentwicklung unterstützen, bei der eine Kombination aus Politik und einer direktiven Rolle des Staates berücksichtigt und im Detail untersucht werden kann.
Keywords: H11; H70; Q48; Q54; Q55; 330; market-shaping; mission-oriented; green finance; renewable energies; transition; entrepreneurial state